Morphological and Syntactic Features of Expression of the Speech Act of Request. - ADAMYAN, VERA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the analysis of one of the important linguistic problems within the framework of the dominant anthropocentric paradigm– speech acts, in particular: the speech act of request. The paper describes the verbal strategies of expressing request in Russian linguoculture, particularly, direct ways of expressing requests. The choice of forms of request depends on the situation of communication. According to the results of the research the most common direct forms of request strategies for the mentioned linguoculture are imperative mood structures.